Exploring the mechanism of immediate analgesic effect of 1-time tuina intervention in minor chronic constriction injury rats using RNA-seq - Wang, Hourong; Liu, Zhifeng; Yu, Tianyuan; Zhang, Yingqi; Xu, Yajing; Jiao, Yi; Guan, Qian; Liu, Di (Frontiers in Neuroscience, 2022)
Previous studies have proved and investigated the mechanism of the analgesic effect of tuina treatment on neuropathic pain. The purpose of this study was to analyze changes in gene expression in the dorsal root ganglia (DRG) and spinal dorsal horn (SDH) after 1-time tuina intervention to investigate the immediate analgesic mechanism by tuina. An improvement in nociceptive behavior in minor chronic constriction injury (CCI) rats after 1-time tuina was observed. 1-time tuina was more effective in the amelioration of thermal hyperalgesia , but no changes were found in the ultrastructure of DRG and SDH. Sixty-five differentially expressed genes (DEGs) modulated by tuina were detected in the DRG and 123 DEGs were detected in the SDH. Potential immediate analgesic mechanisms of tuina were analyzed by the Kyoto Encyclopedia of Genes and Genomes. DEGs were enriched in 75 pathways in DRG, and 107 pathways in SDH. The immediate analgesic mechanism of tuina is related to the calcium signaling pathway, thermogenesis, and regulation of lipolysis in adipocytes.